Motivations and job satisfaction of employees in the Department of Public Works and Highways : fiscal year 2003-2004 - Cailao, Cristita M. (Manila : National University, 2003)
One means of realizing the Department of Public Works and Highway's aim to make administration relevant to the changing world is by improving their relationship with employees, working conditions, adjusting their salaries and enhancing their professional self-concept so that they can function more effectively and efficiently.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Copy of the questionnaire -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.